The Influence of Songs on the Development of English - Syafira, Syafira; Yusriani, Yusriani; Lubis, Yani (Edusifa: Jurnal Pendidikan Islam, 2023)
In an increasingly modern era, the development of English can be carried out by utilizing technological developments to upgrade English skills, one of which is by using music in the form of songs, as a medium for developing English. The song is an art without boundaries that is very enjoyable and is able to make someone express feelings, and convey their message. Songs can be listened to by using several media such as audio media and audiovisual media. Audio media is media in the form of sounds or sounds that can only be heard (auditory) so this media is called listening media and audiovisual media is media that can be seen and heard. Even though using media such as audio and audiovisual there are indicators in choosing a song, namely choosing the right song, choosing the song we like by genre, looking for song lyrics, finding out unfamiliar vocabulary, and singing the song again after understanding and learning the vocabulary in the song. With that, it will make it easier to understand English through songs. Then, the material object is to use audio-visual media, namely the Joox song application and YouTube media with a song called "See You Again". and the object of translation is done through google translate or with online dictionary media. And the researcher concludes, that using songs is a way that is very influential on language development. Key words : Song, audiovisual media